The doctors' 5-minute health fixes : the prescription for a lifetime of great health - Aalst, Mariska van (New York : Rodale, 2010)
The one-stop source for readers looking for comprehensive, top-notch self-care advice and novel, cutting-edge tips, trivia, and information,'The Doctor's 5-minute Health Fixes' will help you vastly improve your health by following very small shifts in your lifestyle.
Includes bibliographical references and index.
Keywords: Health -- Popular Works